2015
DOI: 10.1021/acsami.5b02940
|View full text |Cite
|
Sign up to set email alerts
|

pH-Responsive Shape Memory Poly(ethylene glycol)–Poly(ε-caprolactone)-based Polyurethane/Cellulose Nanocrystals Nanocomposite

Abstract: In this study, we developed a pH-responsive shape-memory polymer nanocomposite by blending poly(ethylene glycol)-poly(ε-caprolactone)-based polyurethane (PECU) with functionalized cellulose nanocrystals (CNCs). CNCs were functionalized with pyridine moieties (CNC-C6H4NO2) through hydroxyl substitution of CNCs with pyridine-4-carbonyl chloride and with carboxyl groups (CNC-CO2H) via 2,2,6,6-tetramethyl-1-piperidinyloxy (TEMPO) mediated surface oxidation, respectively. At a high pH value, the CNC-C6H4NO2 had att… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
99
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 174 publications
(100 citation statements)
references
References 60 publications
1
99
0
Order By: Relevance
“…After application of 10 V direct electric current, the pH value of the solution decreased because of the electrolysis of copper sulfate which in turn was due to the fact that the hook recovered to the original shape and released the weight. Recently, Zhou et al 6,24 and our group 5 reported pHsensitive SMPs that were able to be deformed into predetermined shapes and had the capacity to revert back to its original shape upon application of pH stimulus. Apart from that, it has been demonstrated that hydrophobes can gradually disengage from the hydrophobic associations with increasing temperature, or reassociate at relatively low temperature, enabling reversible change between strong and weak hydrophobic interactions.…”
Section: Acs Applied Materials and Interfacesmentioning
confidence: 96%
“…After application of 10 V direct electric current, the pH value of the solution decreased because of the electrolysis of copper sulfate which in turn was due to the fact that the hook recovered to the original shape and released the weight. Recently, Zhou et al 6,24 and our group 5 reported pHsensitive SMPs that were able to be deformed into predetermined shapes and had the capacity to revert back to its original shape upon application of pH stimulus. Apart from that, it has been demonstrated that hydrophobes can gradually disengage from the hydrophobic associations with increasing temperature, or reassociate at relatively low temperature, enabling reversible change between strong and weak hydrophobic interactions.…”
Section: Acs Applied Materials and Interfacesmentioning
confidence: 96%
“…Shape memory polymers (SMPs) refer to the polymers that stimulate by a variety of stimuli such as electrical current, pH, humidity, magnetic field, heat and light, recovering their original shape. This “memory” feature of SMPs gives them the opportunity to apply in various fields, such as textiles, packaging, medical and aerospace industries .…”
Section: Introductionmentioning
confidence: 99%
“…In medicine fields, a key challenge is that an excess of heat usually causes damage to biological tissue. Nevertheless, water-induced shape memory polymers can effectively compensate for this deficiency [12]. Based on the reported waterinduced shape memory polymer, most of them are made from petroleum chemical raw materials, which are not renewable, biodegradable, and biocompatible [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…Polyethylene glycol (PEG) is a kind of thermoplastic polymer material with high crystallinity and good water solubility, is nontoxic, and is nonirritating, and it has great toughness and good biocompatibility [12,26], making it a good choice to be used as another kind of flexible chain segment of the interpenetrating network structure [27]. Therefore, based on the advantage of the cellulose nanofibers (CNF) with PEG, the CNF and PEG were cross-linked to form a new network shape memory nanocomposite (CNF/PEG/CA) paper, through citric acid (CA) as a crosslinking agent [28].…”
Section: Introductionmentioning
confidence: 99%